Maisy goes to the library - Cousins, Lucy. (Cambridge, Mass. : Candlewick Press, 2009)
Maisy goes to the library in search of a book about fish and a quiet place in which to read it.
"A Maisy first experiences book"--Cover.
First published: London : Walker Books Ltd.
Horn Book
Kirkus Review
School Library Journal
Horn Book, April 2006
Keywords: Animals -- Juvenile fiction; Books and reading -- Juvenile fiction; Libraries -- Juvenile fiction; Maisy (Fictitious character : Cousins) -- Juvenile fiction; Mice -- Juvenile fiction; Quietude -- Juvenile fiction; Animals -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Maisy (Fictitious character : Cousins) -- Fiction; Mice -- Fiction; Quietude -- Fiction; Animals -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Maisy (Fictional character : Cousins) -- Fiction; Mice -- Fiction; Solitude -- Fiction; Picture books for children